A Board Member's Work in Dismantling Systemic Racism. Issue 171 (9th September 2020) - Elsbernd, Cindy
Abstract : Cindy Elsbernd is a governance and leadership coach for Emendable Consulting, LLC. She served two 4‐year terms on the Des Moines Public Schools Board of Directors in Des Moines, Iowa, where she was a board officer for six of those eight years. She is a member of the Council for Great City Schools' "Team Rogue, " a group of school board members and superintendents whose collective research and experience resulted in the development of the Student Outcomes Focused Governance© (SOFG) framework. She is a provisionally certified SOFG Coach and a graduate of Govern for Impact's Policy Governance© Proficiency Program. In this article, she discusses the examination of "white privilege" as the work of boards—white board members in particular—in dismantling systems that perpetuate oppression, suppression, and exclusion; and in developing policy and procedure that create organizational climate and culture for unconditional inclusion. She will be offering workshops for exploring white privilege later this fall.